2017
DOI: 10.1080/1369118x.2017.1402943
|View full text |Cite
|
Sign up to set email alerts
|

Charities’ use of Twitter: exploring social support for women living with and beyond breast cancer

Abstract: Fo r m o r e info r m a tio n, in cl u di n g o u r p olicy a n d s u b mi s sio n p r o c e d u r e , pl e a s e c o n t a c t t h e R e p o si to ry Te a m a t: u si r@ s alfo r d. a c. u k . Charities' use of Twitter|: Exploring social support for women living with and beyond breast cancer.Twitter is one social media platform that enables those experiencing breast cancer to access support from others. This study explores how cancer charities provide support to women living with and beyond breast cancer (LWB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…They found that there was more support than stigma messaging towards mental health or mental illness tweets, however, bipolar disorder related tweets had more stigma and less support than mental health and illness. Ure et al (2019) also found prevalence of tweets with raising awareness themes in support related tweets by cancer charities.…”
Section: Positivementioning
confidence: 82%
See 3 more Smart Citations
“…They found that there was more support than stigma messaging towards mental health or mental illness tweets, however, bipolar disorder related tweets had more stigma and less support than mental health and illness. Ure et al (2019) also found prevalence of tweets with raising awareness themes in support related tweets by cancer charities.…”
Section: Positivementioning
confidence: 82%
“…Budenz et al (2020) found that there was more support than stigma messaging towards mental health or mental illness tweets. Similarly, Ure et al (2019) found prevalence of tweets with raising awareness themes in support related tweets by cancer charities. Furthermore, online social networks have the potential to promote social influence for health and facilitate information sharing platforms (Eghtesadi & Florea, 2020).…”
Section: Positivementioning
confidence: 92%
See 2 more Smart Citations